Perlindungan Terhadap Gaji Dosen Swasta Menurut Undang-Undang Nomor 14 Tahun 2005 Tentang Guru Dan Dosen - mila karmila adi (Fakultas Hukum Universitas Islam Indonesia, 2006)
The article 52 verse (3), the Teacher and Lecturer's Act Number 14 Year 2005, says that a lecturer who works ina private Institution isgiven a payment base dont he work agreement or collective labor agreement. It shows that the private lecturer's payment will beregulated basically on the two party's agreement, the lecturerandthe private institution. Although thereare some provisions that regulate about the payment'details from the Act, some questions will come up In the legal protection to the private lecturer in getting good payment, for example